Students’ Attitudes toward Teachers’ Written Corrective Feedback and Their Writing Skill - Zahroh, Raikhatuz; Mujiyanto, Januarius; Saleh, Mursid (Universitas Negeri Semarang, 2020)
This study aims to explain the students’ behavioral, cognitive, and emotional attitudes toward teachers’ written corrective feedback, as well as the students’ competence in writing skill. It is a quantitative research which was designed to prove the hypothesis with statistical analysis. The population of this study is the 3rd semester students of the English Education program of UNISNU Jepara Indonesia in the academic year of 2018/2019. The questionnaire participants are fifty students of two classes participating as the sample. The interview utilized open-ended questions. To collect data, questionnaire, interview and writing test were applied. In analyzing the data, this study uses SPSS software. The result shows that in the term of the students’ writing skill, the mean score of first test from 50 test takers was 71.1 with the lowest score 52 and highest score 92. The second test shows the mean score was 77.8 and increased 6.7 points. The third test shows the mean score was 80.3 and increased 2.5 points. Thus, there was significant increased mean score from first test to last test. There was positive treatment that given by teacher and the participants’ positive attitude toward teachers’ corrective feedback. Then, the correlation result shows that score with 95% significant level and 50 participant is 0.572. Thus, the correlation between both variables can be categorized as moderate correlation. Therefore, students’ attitudes can give moderate impact to students’ writing skill. In sum, knowing students’ attitude helps the teacher to achieve learning goals.